Insulin-deficient diabetes-induced bone microarchitecture alterations are associated with a decrease in the osteogenic potential of bone marrow progenitor cells: Preventive effects of metformin - Tolosa, María José Anahí (2013)
Aims: Diabetes mellitus is associated with metabolic bone disease and increased lowimpact fractures. The insulin-sensitizer metformin possesses in vitro, in vivo and ex vivo osteogenic effects, although this has not been adequately studied in the context of diabetes. We evaluated the effect of insulin-deficient diabetes and/or metformin on bone microarchitecture, on osteogenic potential of bone marrow progenitor cells (BMPC) and possible mechanisms involved. Methods: Partially insulin-deficient diabetes was induced in rats by nicotinamide/streptozotocin-injection, with or without oral metformin treatment. Femoral metaphysis microarchitecture, ex vivo osteogenic potential of BMPC, and BMPC expression of Runx-2, PPARg and receptor for advanced glycation endproducts (RAGE) were investigated. Results: Histomorphometric analysis of diabetic femoral metaphysis demonstrated a slight decrease in trabecular area and a significant reduction in osteocyte density, growth plate height and TRAP (tartrate-resistant acid phosphatase) activity in the primary spongiosa. BMPC obtained from diabetic animals showed a reduction in Runx-2/PPARg ratio and in their osteogenic potential, and an increase in RAGE expression. Metformin treatment prevented the diabetes-induced alterations in bone micro-architecture and BMPC osteogenic potential. Conclusion: Partially insulin-deficient diabetes induces deleterious effects on long-bone micro-architecture that are associated with a decrease in BMPC osteogenic potential, which could be mediated by a decrease in their Runx-2/PPARg ratio and up-regulation of RAGE. These diabetes-induced alterations can be totally or partially prevented by oral administration of metformin.